Spiritual leadership - Sanders, J. Oswald (John Oswald), 1902-1992 (Chicago : Moody Press, 1994)
With over 500,000 in print, Spiritual Leadership is the perennial favorite for teaching the principles of leadership. In this classic, J. Oswald Sanders illustrates biblical leadership principles through the lives of David, Moses, Nehemiah, the Apostle Paul, David Livingston, and Charles Spurgeon.This world needs more leaders who are guided by God and devoted to Christ. Christianity needs to put forth a powerful voice to be heard above the cacophony of immorality and deception in much of today's leadership. Spiritual Leadership will encourage you to place your talents and powers at His disposal so you can become a leader used for His glory.This timeless classic will equip leaders of all generations to press on in service for Jesus Christ. Spiritual Leadership has easy-to-understand modern language and a study guide to assist each leader as they grow and successfully apply the principles in this book. Prepare to be stretched, challenged, and motivated to apply the leadership principles of character, passion, and especially godliness. Spiritual Leadership is a necessary tool for today's leaders. -- Amazon.com
An honorable ambition -- The search for leaders -- The master's master principle -- Natural and spiritual leadership -- Can you become a leader -- Insights on leadership from Paul -- Insights on leadership from Peter -- Essential qualities of leadership -- More essential qualities of leadership -- Above all else -- Prayer and leadership -- The leader and time -- The leader and reading -- Improving leadership -- The cost of leadership -- The responsibilities of leadership -- Tests of leadership -- The art of delegation -- Replacing leaders -- Reproducing leaders -- Perils of leadership -- The leader Nehemiah
"Completely updated text with study guide."
Includes bibliographical references and indexes
Keywords: Christian leadership